2017
DOI: 10.1111/cod.12822
|View full text |Cite
|
Sign up to set email alerts
|

Non‐mix fragrances are top sensitizers in consecutive dermatitis patients – a cross‐sectional study of the 26 EU‐labelled fragrance allergens

Abstract: Non-mix fragrances are the most important single fragrance allergens among consecutive patients. The test concentration of the single FM I constituents should be increased when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
75
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 37 publications
14
75
2
Order By: Relevance
“…In a Danish study investigating the relevance of positive patch test reactions, contact allergy to cinnamyl alcohol was reported to be relevant in 80% of the cases, whereas contact allergy to cinnamal was reported to be relevant in 45% of the cases . Contact allergy to cinnamal and cinnamyl alcohol is not decreasing among dermatitis patients, as the frequencies of contact allergy were found to be the same in 2017 as in previous studies . In the general population, the frequencies of contact allergy to cinnamal and cinnamyl alcohol have been found to be 0.8% and 0.3%, respectively .…”
Section: Introductionmentioning
confidence: 69%
“…In a Danish study investigating the relevance of positive patch test reactions, contact allergy to cinnamyl alcohol was reported to be relevant in 80% of the cases, whereas contact allergy to cinnamal was reported to be relevant in 45% of the cases . Contact allergy to cinnamal and cinnamyl alcohol is not decreasing among dermatitis patients, as the frequencies of contact allergy were found to be the same in 2017 as in previous studies . In the general population, the frequencies of contact allergy to cinnamal and cinnamyl alcohol have been found to be 0.8% and 0.3%, respectively .…”
Section: Introductionmentioning
confidence: 69%
“…Results from this cross-sectional study showed that out of 6004 patients, 940 were patch positive to one of these fragrances. Among these 940 patients, most of them showed patch positive reactions to linalool-hydroperoxides [110]. A recent case report described a 45-year-old woman from Sweden who suffered from an eczematous reaction after she wore Footner ® exfoliating socks' (Nordic Consumer Health, Nacka Strand, Sweden) on both feet for one hour as it was stated in the instructions.…”
Section: Linaloolmentioning
confidence: 99%
“…Ideally, the discussion on inclusion should consider clinical relevance of positive reactions, in particular, as at least some of the weak‐positive reactions (erythema and infiltration) may be irritant. Reassuringly, the above‐mentioned Copenhagen study based on 6004 consecutive patients has found clinical relevance in about 75% of patients, which is similar to other fragrance allergens.…”
mentioning
confidence: 62%
“…follow up on an earlier study, presenting patch‐test results obtained in 2015/16 at St John's in 2084 consecutively tested patients, now using oxidized linalool and limonene. This had an enormous impact on results, with 7·4% (4·3%) positive reactions to oxidized linalool (limonene), even higher than the 3·9% and 2·5%, respectively, recently reported from Copenhagen . As elsewhere, fairly limited ‘overlap’ between positive reactions to the oxidized terpenes and the remaining fragrances, including baseline series markers, was observed.…”
mentioning
confidence: 72%